Mompreneur-Based Online Business Supports the Family Economy During the Covid-19 Pandemic - Inanna, Inanna; Suharni, Suharni; Supatminingsih, Tuti; Nurjannah, Nurjannah; Hasan, Muhammad (Economic Education and Entrepreneurship Journal, 2023)
This study aims to determine the Mompreneur strategy in online business during the covid 19 era so that online business is able to support the family economy in Mangarabombang District, Takalar Regency. This research was conducted using qualitative methods and descriptive approaches and data collection through observation, interviews with 5 informants and documentation. The result of this study proves that by running an online business during the covid 19 pandemic, Mompreneurs can support the family economy by implementing various online business strategies such as promotions, transactions and marketing.Keywords: Family Economy, Mompreneurs, online Business, Pandemic Covid 19DOI: http://dx.doi.org/10.23960/E3J/v6i1.22-30